Pengaruh Insentif Terhadap Motivasi Kerja Karyawan Pada PT. Saerah Surya Perkasa Surabaya - Ima Ismatul Khasanah; Komarun Zaman (STIKes Ibnu Sina Ajibarang, 2023)
The purpose of this study was to determine whether incentives affect employee motivation at PT Saerah Surya Perkasa Surabaya, to determine how much influence incentives have on employee motivation at PT Saerah Surya Perkasa Surabaya. In this thesis research, the sample used is simple ramdom sampling, namely random sampling without regard to level and the population in this study amounted to 100 people. This study uses primary and secondary data. Data collection techniques using observation and questionnaires. The analysis technique used is quantitative. The results of this study are, Data is analyzed by validity test, reliability test and simple regression test (t test) using SPSS 20 for windows application. The results showed that incentives had an influence on employee work motivation and the magnitude of the influence of incentives on employee work motivation at the regent's office of Southwest Aceh Regency was 10.0%.